Linguistic embodiment and verbal constraints: human cognition and the scales of time - Cowley, Stephen J. (Frontiers in Psychology, 2014)
Using radical embodied cognitive science, the paper offers the hypothesis that language is symbiotic: its agent-environment dynamics arise as linguistic embodiment is managed under verbal constraints. As a result, co-action grants human agents the ability to use a unique form of phenomenal experience. In defence of the hypothesis, I stress how linguistic embodiment enacts thinking: accordingly, I present auditory and acoustic evidence from 750 msec of mother-daughter talk, first, in fine detail and, then, in narrative mode. As the parties attune, they use a dynamic field to link their co-embodiment with experience of wordings. These arise from making and tracking phonetic gestures that, crucially, mesh use of artifice, cultural products and impersonal experience. As observers, living human beings gain dispositions to display and use social subjectivity. Far from using brains to ‘process’ verbal content, linguistic symbiosis grants access to diachronic resources. On this distributed-ecological view, language can thus be redefined as: “activity in which wordings play a part”.